“FOIL”
(x+a)(x+b)
=x^2+(b+a)x +ab
“Difference of Squares”
a^2-b^2= (a+b)(a-b)
a^2+2ab+b^2=(a+b)(a+b)
a^2-2ab+b^2=(a-b)(a-b)
“Reverse FOIL”
x^2+(b+a)x+ab= (x+a)(x+b)
You can use Reverse FOIL to factor a polynomial by thinking about two numbers a and b which add to the number in front of the x, and which multiply to give the constant. For example, to factor x^2+5x+6, the numbers add to 5 and multiply to 6, i.e.:
a=2 and b=3, so that x^2+5x+6=(x+2)(x+3).
To solve a quadratic such as x^2+bx+c=0, first factor the left side to get (x+a)(x+b)=0, then set each part in parentheses equal to zero.
For example, x^2+4x+3= (x+3)(x+1)=0 so that x=-3 or x=-1.
To solve two linear equations in x and y: use the first equation to substitute for a variable in the second. E.g., suppose x+y=3 and 4x-y=2. The first equation gives y=3-x, so the second equation becomes 4x-(3-x)=2 ⇒ 5x-3=2 ⇒ x=1,y=2.